Karta proliva Seni︠a︡vinʺ (vʺ Beringovom prolivi︠e︡) sostavlena sʺ opisi Kapitana Litke 1828 g. i popolena sʺ kartʺ Leĭtenanta Onat︠s︡evicha 1876 g. amerikanskoĭ Leĭt. Rodzhersa 1855 g. i anglīĭsk. N. 1231 izd. 1898 g. / Chertilʺ tushi︠u︡i︠u︡ M. Psisi︠e︡evʺ - Soviet Union. Gidrograficheskoe upravlenie (Sankt-Peterburg : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; [Санкт-Петербург] : Морское министерство, Главное гидрографическое управленіе, 1902)
Relief shown by from lines. Depths shown by gradient tints, soundings and isolines.; Includes inset map.; Main title translation: Map of Senyavin Strait (in the Bering Strait) compiled from the survey of Captain Litke in 1828 and supplemented from the maps of Lieutenant Onatsevich of 1876 and the American Lieutenant Rogers of 1855 and British chart n. 1231 of 1898.; Top margin title translation: Eastern Sea, Bering Sea.; "Masshtabʺ 2,6 milʹ vʺ di︠u︡ĭmi︠e︡" = Scale 2.6 miles in 1 inch.; Greenwich meridian.; "No. 590" -- margins Color; 1:165,000